The importance of personal data protection in Indonesia’s economic development - Ari Wibowo; Widya Alawiyah; Azriadi (Cogent Social Sciences, 2024)
The aim of this study is to analyze the importance of personal data protection in economic development. To sharpen the analysis, a case study was conducted on consumer’s personal data breaches of Tokopedia as one of the largest digital marketplaces in Indonesia. Using the normative (doctrinal) type of legal research, this study examined legal materials obtained through documentary research and literature review. This paper also used statutory approaches, conceptual approaches, and case approaches. The results of this study indicate that Tokopedia data breach of its user accounts to be traded on the dark web significantly results in a crisis of consumer confidence in Tokopedia. In a broader sense, digitization in economic activities that makes personal data a state asset, especially in the economic sector because it has a direct impact on economic development, has necessitated the guarantee on personal data protection, which certainly has a positive effect on the economic development of a country. So that cases like what happened to Tokopedia do not happen again, digital marketplaces must provide a set of systems that guarantee compliance with personal data protection regulation. The government must also strictly enforce personal data protection regulation.